Cracks developed during SrTiO3 thin-film preparation from polymeric precursors - Zanetti, S. M.; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Wiley-Blackwell, 1999)
Strontium titanate (SrTiO3) thin films were prepared by dip-coating Si(111) single-crystal substrates in citrate solutions of ethylene glycol, considering several citric acid/ethylene glycol (CA/EG) ratios. Measurements of intrinsic viscosity indicate that increasing the amount of EG increases the precursors' polymeric chains and increases the weight loss. After deposition the substrates were dried on a hotplate (approximate to 150 degrees C); this was followed by heat treatment at temperatures ranging from 500 to 700 degrees C using heating and cooling rates of 1 degrees C min(-1). SEM and optical microscopy investigations of the sintered films obtained from different CA/EG ratios indicate that there is a critical thickness above which the films present cracks. This critical thickness for SrTiO3 films deposited on the Si(111) substrate is about 150 nm, Measurements of crack spacing as a function of film thickness indicate that the origin of cracks cannot be explained by the elastic behavior of the film but rather by the viscoelastic relaxation of the film during pyrolysis and sintering. Copyright (C) 1999 John Wiley & Sons, Ltd.
Keywords: sol gel process; thin films; strontium titanate; cracking; ethylene glycol; citric acid